# Non amplifiing circuit (OP)

• Engineering

## Homework Statement

Analyze the ideal op-amp circuit shown in figure to find an expression for v0 in terms of vA,vB and the resistance values.

## Homework Equations

if i label the voltage across R1 as V1
then vi know that v1=R1/(R1+R2) *v0
but i need one more expression for v1.
i tried to use kvl in the lope (with Va,Ra and R1) but couldn't solve because of resistance Ra

## The Attempt at a Solution

#### Attachments

• 21.7 KB Views: 331
Last edited:

Related Engineering and Comp Sci Homework Help News on Phys.org
Zryn
Gold Member
What are the two basic rules governing ideal Op-Amps? (Hint: Use the voltage one, not the current one)

what do u meen with use Use the voltage one?
i tried using kvl on all the loops but coudn't solve.
current goin in to the + on the amp =0 and voltage is 0 between + and - on the amp. summing point constraint.

The voltage at each of the op-amp's inputs is = V1. It's just a fact about ideal op-amps.

is there any way to show that
But then should i use KVL at amp node=

The current going into each input = 0 and the voltage is the same at each input. It's true for inverting and non-inverting.

And one more question in an amplifing circuit is the input impedance =0 or is is it infinity
or does it depend on the other facts.
We have a voltage source directy connected to + or - on the amp
but it woulden't be op-amp's inputs is = V1. for noninvering amp because R1 doen't exist in non inverting.

Well, I think I have given you too many free answers haha.

Just use Ohm's law and you can figure out the input impedance. I = V/R. To get 0 current, your R must be ???

Then you would have the same voltage on the other input if it is directly connected, they are always the same.

i just want to know why the get Rin =0
because WesleyPipes said i=v/R
I=0 if R=--->infinity or if v=0
we know that v is zero
but R can't be zero

Calculation is simple.

Va-V1)/Ra + Vb-V1)/Rb = 0
Solving, V1= [(Va/Ra) + (Vb/Rb)] / [(1/Ra) + (1/Rb)]

Now, Vo = [1+ (R2/R1)]V1
Substitute and you will get the answer.